The Effect of the BI Rate, Inflation and Exchange Rates on Consumer Goods Stock Prices - Murtiningrum, Widiastuti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
In the midst of the current economic conditions, with an increase in Bank Indonesia's interest rates, consumer sector stocks became the main choice for investors, because they are defensive stocks. Investors tend to accumulate stocks in this sector, after the post-Covid economic recovery has occurred, the public has the potential to increase consumption, this is expected to have an impact on the condition of consumer goods stocks. The capital market has a very important role for all sectors, both private, government and society in general. Investors must pay attention to macroeconomic variables including Bank Indonesia interest rates, inflation and the Rupiah exchange rate. Under these conditions, research was conducted with the aim of analyzing, testing and concluding the influence of the BI Rate, Inflation, and the Rupiah exchange rate on consumer goods stock prices on the Indonesian Stock Exchange for the period 2018 – 2022. Using secondary data on companies listed on the Indonesia Stock Exchange, has complete financial reports, has stock price information from January 2018 to October 2022. Analysis data is processed using multiple linear regression and classical assumption tests with quantitative analysis techniques using SPSS 25. The results show simultaneously the influence of the BI Rate, Inflation, Rupiah exchange rate against consumer goods stock prices.